The Model of Relationships between Intellectual Capital, Learning Organizations, and Innovation-Oriented Organizational Structures in Educational Organizations - ÇETİN, MÜNEVVER (ANI YAYINCILIK, 2021)
Purpose: To gain an advantage in a rapidly changing competitive environment, organizations should be aware of their invisible and hard-to-imitate assets as well as their tangible assets. The survival skills of organizations that discover and enrich their abilities are increasing. Therefore, it is important to consider the intellectual capital of the organizations, the learning organizations, and the innovation-oriented organizational structure. This research aims to model the relationship between the intellectual capital of educational organizations, the learning organization, and the innovation-oriented organizational structure. Research Methods: The Structural Equation Model (SEM) was used to reveal the relationship patterns between the variables in the study. Five hundred and fifty-three school administrators and teachers voluntarily participated in the study. Three different scales were used to collect data, these were: The Intellectual Capital Scale, The Learning Organization Scale, and The Innovative School Scale. The mediation model was tested to determine the relationship patterns between learning organizations, innovation-oriented organizations, and intellectual capital based on the educational organizations' perceptions. Findings: The structure between the learning organizational structure of educational organizations and the organizational structure focused on intellectual capital and innovation, were found to be positively and highly significant. It has been determined that the intellectual capital of educational organizations has a partial intermediary role between the learning organizations and the innovation-oriented organizations. Implications for Research and Practice: According to the structural equality model used to reveal the relationship patterns between the three variables, the findings show that the learning organizational structure of educational organizations indirectly affects innovation-oriented organizations through intellectual capitals. Building educational organizations as learning organizations is effective for their innovation-oriented structure. These organizations that value intangible assets such as intellectual capital, will ensure the development and effectiveness of human, structural, and relational capitals. (C) 2021 Ani Publishing Ltd. All rights reserved
Keywords: Intellectual capital; learning organization; innovation; learning; VALUE CREATION; STRATEGIES; ORIENTATION; MANAGEMENT; CULTURE